HUBUNGAN GAMBARAN HISTOPATOLOGI DENGAN GAMBARAN KLINIS KANKER OVARIUM DI RSUP DR. M. DJAMIL PADANG 2018-2019 - Putri, Ratih Elsa; Yenita, Yenita; Yusrawati, Yusrawati (SINERGI : Jurnal Riset Ilmiah, 2025)
Background: Ovarian cancer is a gynecological malignancy with high mortality rate because it has non-spesific symptoms so that it is often not detected on early stage and has a poor prognosis. Gynecological physical exam, ultrasound, and CA-125 test can help to diagnose ovarian cancer.  Objectif:  This study aims to analyze the association between the type of histopathological features with the clinical features of ovarian cancer at dr. M. Djamil Padang Hospital in 2018-2019. Methods: This study was an analytic study with a cross sectional approach using retrospective data. The sampling technique was total sampling. This research was carried out by taking data from medical record of ovarian cancer patients at dr. M. Djamil Padang Hospital in 2018-2019. This research was conducted from March  2020 to December 2022 with a sample of 25 patient. Analysis of the data used in the form of univariate analysis and bivariate analysis using Fisher’s exact test. Results: This study found that there was no assoaciation between histopathological type of ovarian cancer with bloating (p=0,607), abdominal/pelvic pain (p=0,704), difficulty eating (p=0,607), urinary frequency (p=0,607), advanced stage clinical symptoms (p=0,193), adnexal masses (p=0,286), ultrasound with IOTA Simple Rules (p=0,704), and tumor marker test CA-125 (p=0,296). There was significant association between histopathological type of ovarian cancer with ascites (p=0,043). Conclusion: Clinical symptoms,gynecological physical exam, ultrasound, and tumor marker test CA-125 in ovarian cancer patient did not have association with histopathological type